GC-MS Based Metabolic Profiling of Parkinson’s Disease with Glutathione S-transferase M1 and T1 Polymorphism in Tunisian Patients - Rebai, Amal; Reçber, Tuba; Nemutlu, Emirhan; Chbili, Chahra; Kurbanoglu, Sevinç; Kir, Sedef; Amor, Sana B.; Özkan, Sibel A.; Saguem, Saad (Combinatorial Chemistry & High Throughput Screening, 2020)
Aim and Objective: Parkinson’s disease (PD) is the second most common neurodegenerative disease. It is a multifactorial disorder (caused by aging, environmental, and genetic factors). Metabolomics can help explore the biomarker profiles for aging. Recent studies showed an association between the glutathione S-transferases (GSTs) polymorphisms and PD risk. The purpose of this study was to evaluate the association of this genetic polymorphism and the metabolomic profile in PD Tunisian patients, in order to identify effective biomarkers in the genetic differentiation. Materials and Methods: In this study, the metabolomic profile changes related to GSTs polymorphism were searched in 54 Tunisian PD patients treated with L-dopa, using a gas chromatography-mass spectrometry (GC-MS) technique. Results: The study results showed that mannose, methyl stearate, and three other unknown metabolites, increased in patients with GSTM1 positive genotype, while glycolic acid, porphine, monomethyl phosphate, fumaric acid, and three other unknown metabolites decreased in patients with GSTM1 positive genotype. Subsequently, the levels of glycolic acid, erythronic acid, lactic acid, citric acid, fructose, stearic acid, 2-amino-2-methyl-1,3-propanediol and three other unknown metabolites increased in patients with GSTM1 positive genotype, while the levels of proline, valine and two unknown metabolites decreased with GSTT1 positive genotype. Conclusion: All these altered metabolites are related to energy metabolism and it can be concluded that GSTs polymorphism based the shifting in energy metabolism and led to oxidative stress.
Keywords: Parkinson' s disease